2006
DOI: 10.1016/j.febslet.2006.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human low‐density lipoprotein receptor as a novel target gene regulated by liver X receptor alpha

Abstract: Liver X receptor alpha (LXRa) is a member of the nuclear receptor superfamily that is activated by oxysterols, and plays a pivotal role in regulating the metabolism, transport and uptake of cholesterol. Here, we demonstrate that LXRa also regulates the low-density lipoprotein receptor (LDLR) gene, which mediates the endocytic uptake of LDL cholesterol in the liver. An LXR agonist induced the expression of LDLR in cultured hepatoblastoma cells. Moreover, the LDLR promoter contained an LXR response element that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Here we showed that the LXR agonist TO901317 is an activator of PCSK9 in human cells. As published recently, it also induced LDLr transcription (49). Interestingly, we found an additive effect of both drugs on LDLr regulation.…”
Section: Discussionsupporting
confidence: 69%
“…Here we showed that the LXR agonist TO901317 is an activator of PCSK9 in human cells. As published recently, it also induced LDLr transcription (49). Interestingly, we found an additive effect of both drugs on LDLr regulation.…”
Section: Discussionsupporting
confidence: 69%
“…The mature human SREBP-1c expression vector (pcDNA3-nSREBP1c, amino acids 1-436) was created by cloning the appropriate cDNA from HepG2-tet-off-hLXR␣ cells into the pcDNA3 vector (21). The murine NF-YA29-expressing plasmid (pcDNA3-NF-YA29) has been described previously (22).…”
Section: Methodsmentioning
confidence: 99%
“…The membrane-bound FATPs, FABPpm and CD36, and intracellular FABPs have so far been believed to be the lipid uptake from lipoproteins is well documented ( 45,46 ), but little information is available regarding their role in cellular fatty acid activation and fatty acid uptake per se. This article demonstrates that activation of LXR increases acyl-CoA synthetase activity through transcriptional activation of ACSL3 expression.…”
Section: Lxr Agonist Increases Fatty Acid Uptake In Bewo Cellsmentioning
confidence: 99%